745. Surveillance for Oseltamivir-Resistant Influenza A(H1N1)pdm09 Virus Infections During 2016–2017 and 2017–2018, United States. (26th November 2018) - Spencer, Sarah; Nguyen, Ha; Elal, Anwar Abd; Laplante, Jennifer; George, Kirsten St; Fry, Alicia M; Gubareva, Larisa; Campbell, Angela P
Abstract: Background: Three neuraminidase inhibitors (NAIs) are approved and recommended for treatment of influenza in the United States; however, antiviral resistance can emerge during or after treatment, and sporadic resistant viruses unrelated to NAI exposure may occur, especially in influenza A(H1N1)pdm09 viruses. Limited transmission of oseltamivir-resistant A(H1N1)pdm09 viruses between persons has also occurred. Oseltamivir resistance is most commonly caused by an H275Y substitution in the neuraminidase (NA). We describe findings from surveillance for oseltamivir-resistant A(H1N1)pdm09 viruses. Methods: The CDC requested state public health laboratories to submit up to eight viruses (two of each subtype/lineage) every 2 weeks for virus sequencing and NA inhibition assay testing; up to five additional A(H1N1)pdm09 clinical specimens were requested for H275Y pyrosequencing. NA sequencing and functional phenotypic NA inhibition assays were performed on drug-resistant virus isolates. A standard case form was collected on persons infected with oseltamivir-resistant viruses. Results: From October 1, 16 to April 18, 18, 1, 368 A(H1N1)pdm09 viruses were tested (median 89 specimens, range 20–328, tested/month during the influenza season). Overall, 12 ( 0.9%) oseltamivir-resistant A(H1N1)pdm09 viruses were detected from nine states; all contained H275Y in the NA. All viruses were also resistant to peramivir, but none to zanamivir. The 12 patients had a median age of 34 years (range, 2 months–69 years). Eight (67%) had an immunosuppressive condition. Six (50%) reported no exposure to NAIs before specimen collection, two were taking oseltamivir (for 1 and 20 days) at the time of specimen collection, and antiviral receipt was unknown for 4. Three (23%) patients were hospitalized; there were no deaths. Conclusion: During the 2016–2017 and 2017–2018 influenza seasons, influenza A(H1N1)pdm09 viruses resistant to both oseltamivir and peramivir were infrequently detected; all retained susceptibility to zanamivir. Among those with available information, half had no exposure to oseltamivir. Viruses harboring H275Y continue to circulate at low levels in the community. Ongoing surveillance for trends in oseltamivir- and peramivir-resistant A(H1N1)pdm09 is critical to inform clinical care and public health policies. Disclosures: All authors: No reported disclosures.